Bidirectional risk between venous thromboembolism and cancer in East Asian patients: synthesis of evidence from recent population-based epidemiological studies - Kok VC (Cancer Management and Research, 2017)
Victor C Kok1,2 1Division of Medical Oncology, Cancer Center, Kuang Tien General Hospital, 2Asia University, Taichung, Taiwan Background: Unprovoked (idiopathic) venous thromboembolism (VTE) with no obvious antecedent risk factors, is associated with a significant risk of subsequent occult cancer. Conversely, there is a heightened risk of VTE in cancer patients. This bidirectional risk can be estimated from population-based cohort studies conducted in East Asians. Methods: A literature search using medical subject heading terms and Boolean logic in PubMed and MedLine was performed in April 2017. Twenty-two papers reported from East Asia were retrieved for study and data synthesis. Proportional meta-analysis with a random-effects model was used to synthesize data with 95% confidence intervals (CIs) when appropriate. Results: Synthesis of data on VTE incidence in the East Asian population (I2 = 76.2%) showed that pooled incidence was 20.3 (95% CI, 11.2–32) per 100,000 person-years. VTE incidence steadily increased with age. Unprovoked VTE accounted for 35% (95% CI, 24%–48%) of all cases of incident VTE (I2 = 99.7%). The overall cancer risk was significantly higher (2.3-fold) in the VTE cohort than in comparators. Among the patients with unprovoked VTE, approximately 7% had a subsequent cancer diagnosis within 2 years of the first episode of idiopathic VTE. The risk of VTE recurrence was increased in cancer patients (adjusted odds ratio, 1.64; 95% CI, 1.26–1.99). VTE incidence was 9.9 per 1,000 person-years in cancer patients, particularly in liver, pancreas, and lung cancer patients. Conclusion: Newly diagnosed VTE incidence is estimated at approximately 4,400 new cases annually in Taiwan and 7,100 in South Korea. Similar to the trend in VTE incidence among the general population, VTE risk in East Asian cancer patients is markedly lessened. Keywords: venous thromboembolism, cancer, East Asian, bidirectional relationship, epidemiological study